2005
DOI: 10.1002/bdra.20190
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol exposure and early postnatal changes in the developing nerve-muscle system

Abstract: The finding that a higher proportion of endplates were polyneuronally innervated in the alcohol-exposed rats indicates that the maturation process of the neuromuscular system was delayed, thus confirming the deleterious effects of alcohol on growth and maturation of the nerve-muscle system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…As reported in an earlier study (David and Subramaniam, 2005), the body weight of the offspring showed no significant difference (p > 0.1) at birth (day 0 to 1). However, weights of alcohol-exposed animals were significantly lower (p < 0.05) than those of the control rats when studied 1 to 4 weeks after birth (Fig.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…As reported in an earlier study (David and Subramaniam, 2005), the body weight of the offspring showed no significant difference (p > 0.1) at birth (day 0 to 1). However, weights of alcohol-exposed animals were significantly lower (p < 0.05) than those of the control rats when studied 1 to 4 weeks after birth (Fig.…”
Section: Resultssupporting
confidence: 66%
“…As documented in earlier studies (David and Subramaniam, 2005), no significant difference was noted in the number of pups per litter between the control and alcohol-exposed groups of rats, and the mean BAC was maintained at 98.3 6 8.0 mg/dl. However, a significant difference in maternal body weight gain was obtained, whereby the dams in the alcohol-exposed group gained significantly less weight (p < 0.05) over the course of gestation when compared with the control group.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Neuroimaging studies show that structural brain damage resulting from PAE may be extensive and persistent [14]. Structures that control motor function may be damaged by PAE, including structures in the central nervous system (cerebellum, corpus callosum and basal ganglia) [15,16] and peripheral nervous systems (muscle fibres, motor neurons and myelin) [17][18][19]. In the limited studies available, motor deficits have been demonstrated following PAE at ≥10 standard drinks per week but have not been demonstrated following lowerlevel PAE [20], and the effects of binge drinking are inconclusive [20].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, using sTMS in selected areas of the motor cortex to calculate the amount of current necessary to produce a response in an EMG electrode, Dr. Rotenberg demonstrated how cortical excitability matures with age. Dr. Rotenberg called attention to animal studies that showed decreased myelination after developmental alcohol exposure (David & Subramaniam, 2017), and noted that it would be interesting to use the non-invasive sTMS approach to evaluate the state of the maturation of excitability and nerve conductivity in subjects with FASD. Another alteration of cortical excitability that is common in subjects with FASD is epileptic seizures (Bell et al, 2010; Nicita et al, 2014).…”
Section: Keynote Presentationsmentioning
confidence: 99%